The Role of Exosomes and Exosomal Noncoding RNAs From Different Cell Sources in Spinal Cord Injury - Yang, Zhe-Lun; Rao, Jian; Lin, Fa-Bin; Liang, Ze-Yan; Xu, Xiong-Jie; Lin, Yi-Ke; Chen, Xin-Yao; Wang, Chun-Hua; Chen, Chun-Mei (Frontiers in Cellular Neuroscience, 2022)
Spinal cord injury (SCI) not only affects the quality of life of patients but also poses a heavy burden on their families. Therefore, it is essential to prevent the occurrence of SCI; for unpreventable SCI, it is critical to develop effective treatments. In recent years, various major breakthroughs have been made in cell therapy to protect and regenerate the damaged spinal cord via various mechanisms such as immune regulation, paracrine signaling, extracellular matrix (ECM) modification, and lost cell replacement. Nevertheless, many recent studies have shown that the cell therapy has many disadvantages, such as tumorigenicity, low survival rate, and immune rejection. Because of these disadvantages, the clinical application of cell therapy is limited. In recent years, the role of exosomes in various diseases and their therapeutic potential have attracted much attention. The same is true for exosomal noncoding RNAs (ncRNAs), which do not encode proteins but affect transcriptional and translational processes by targeting specific mRNAs. This review focuses on the mechanism of action of exosomes obtained from different cell sources in the treatment of SCI and the regulatory role and therapeutic potential of exosomal ncRNAs. This review also discusses the future opportunities and challenges, proposing that exosomes and exosomal ncRNAs might be promising tools for the treatment of SCI.